Guía metodológica para la gestión del talento humano con discapacidad en la Universidad Politécnica Salesiana Sede Quito. - Miniguano Rodríguez, Jonathan Santiago (2014)
The analysis of the workers with disability situational reality, added to the theoretical base taken from authors as: Kurt Goldstein, Abraham Maslow, Alfred Adler and the legal sustenance that international and state organizations give us, lead us to the creation of a Methodological Guide for human talent with disabilities management in the Salesian Polytechnic University. The product that appears later is directed to the human talent management, it has as principal purpose offering limits of action, in order to achieve the inclusion of persons with disabilities in work environments. For the development of the idea, first it is necessary to define types of disability, with a brief explanation of its characteristics and the recommendations for relationships. This information provides knowledge about this topic, offering confidence for social interrelationships that are formed in this space. Directed to the processes of human talent in an organization, the guide proposes a model of management sustained from three important interdependent core ideas: Insertion, Integration and Incorporation. Each of these main ideas contain procedures that respect a time designated to a stage and these at the same time are developed by tools that facilitate the scope of the immediate goals in the mentioned stage and allow to continue to the next one. To follow this protocol, offers a process which long-term results present a panorama of total inclusion in a work environment.